2021
DOI: 10.1002/ece3.8165
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide selective detection of Mile red‐bone goat using next‐generation sequencing technology

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Yuan and co-authors were the first to utilize resequencing technology to establish a CNV map of Chinese fine-wool sheep and analyzed the overlap of CNVRs with several quantitative trait loci related to economic traits, providing vital insights for the future improvement of fine-wool sheep ( 110 ). Consistently previous studies employed resequencing to analyze the genomic CNVs of Mile red-boned goats and African goats, respectively ( 64 , 65 ). These findings facilitated a deeper understanding of the genetic traits of these animals.…”
Section: Overview Of Screening Methods For Cnvs In Herbivorous Livest...supporting
confidence: 67%
“…Yuan and co-authors were the first to utilize resequencing technology to establish a CNV map of Chinese fine-wool sheep and analyzed the overlap of CNVRs with several quantitative trait loci related to economic traits, providing vital insights for the future improvement of fine-wool sheep ( 110 ). Consistently previous studies employed resequencing to analyze the genomic CNVs of Mile red-boned goats and African goats, respectively ( 64 , 65 ). These findings facilitated a deeper understanding of the genetic traits of these animals.…”
Section: Overview Of Screening Methods For Cnvs In Herbivorous Livest...supporting
confidence: 67%
“…However, the results of this study showed non-significant differences in genotype and allele frequencies of the identified SNPs and copy number of EDN3 gene among blackboned and non-black-boned sheep. Interestingly, a different bone pigmentation, e.g., red pigmentation, has also been described in goats [103][104][105]. Such pigmentation characteristics might influence carcass quality and standards and, subsequently, consumer preference.…”
Section: Black Bone Color or Hyperpigmentationmentioning
confidence: 99%
“…As compared to SNP mutations, the CNV fragments are large in length and cover a wider range of genomes that have broader prospects in studying animal genetics and breeding application. Recently, next-generation genome sequencing technologies have been continuously used to detect the genome-wide CNVs of livestock (8,9). However, numerous genomic studies exploring CNVs in commercial cattle breeds have underestimated the role of native breeds in the adaptation process (10,11).…”
Section: Introductionmentioning
confidence: 99%